The New Regulations on Land Management Rights (HPL) to Increase Investment - Dwiyatmi, Sri Harini; Hutajulu, Marihot Janpieter; Novitasari, Selvie; Amitha, Exsa Nur Chika (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Land Management Rights (HPL) are an agrarian legal instrument that plays a strategic role in managing state assets. However, procedural complexity, overlapping regulations, and limited investor access to state land often hinder the creation of a conducive investment climate. The government introduced new regulations regarding HPL to address these issues by strengthening legal certainty, simplifying cooperation mechanisms, and increasing transparency. This article aims to examine the substance of the new HPL regulations and analyze their implications for increasing investment in Indonesia. The research uses a normative juridical method with a legislative approach and qualitative analysis of policy documents and implementation practices. The study results indicate that the new regulations provide greater flexibility for HPL holders in collaborating with investors while simultaneously reducing bureaucratic obstacles. However, challenges such as harmonizing regulations and protecting surrounding communities still require attention to ensure sustainable investment growth.